Determinan Faktor Yang Memengaruhi Minat Wajib Pajak Dalam Penggunaan E-Filing (Studi Empiris Pada KPP Pratama Jayapura) - Muslimin, Ulfah Rizky; Falah, Syaikhul; Tandililing, Elia Madatu; Puspitasari, Esti Diah (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2023)
This research aims to determine the influence of perceived usefulness, perceived convenience, perceived security and confidentiality on taxpayer interest in using e-filing at KPP Pratama Jayapura City. The dependent variable used in this research is taxpayer interest in using e-filing, while the independent variables are perceived usefulness, perceived convenience, perceived security and confidentiality. The respondents are individual taxpayers who have used e-filing and have not used e-filing at KPP Pratama Jayapura City. This research uses multiple linear regression analysis with a sample of 100 respondents. The results show that perceived usefulness influences taxpayers' interest in using e-filing, perceived ease influences taxpayers' interest in using e-filing, perceptions of security and confidentiality influence taxpayers' interest in using e-filing, as well as perceived usefulness and ease of use. , perceptions of security and confidentiality jointly influence taxpayers' interest in using e-filing. Keywords ; Confidentally, Convenience, E-filling, Perceived Usefulness, Security, and Taxpayer